Aplikasi Android Sahabat Kanker Untuk Meningkatkan Kualitas Tidur Pada Pasien Kanker - Darmawan, Rendi Editya; Astuti , Duwi Pudji (Jurnal Perawat Indonesia, 2021)
Background: Insomnia or sleep disorders are a major problem in cancer patients. Interventions for early detection of sleep disorders using the Pittsburgh Sleep Quality Index (PSQI) instrument, Al Quran Surah Yasin and Ayat Kursi, patterns of physical activity and diet for cancer patients through the cancer companion application have the potential to improve patient sleep quality. Objective: to analyze the effect of the cancer companion android application in improving the sleep quality of cancer patients. Research method: quantitative pre-experiment with 1 group, conducted in February-November 2021 at Dr Moewardi Hospital Surakarta. The population of cancer patients was 82 respondents, and calculated using a paired numerical sample analysis formula, obtained a sample of 68 respondents. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) instrument on the first day of hospital admission, then intervention using the cancer companion application was carried out for 5-6 days. Data analysis compared sleep quality on day 1 and day 6 with the Wilcoxon test. Results: The results of the Wilcoxon test showed an asymp.sig 0.04, which means that there is a difference in the quality of sleep between patients before and after the intervention. Most of the sleep quality increased from a dominant level of moderately satisfied (79%), to a dominant level of very satisfied (44%), and satisfied (38%). Conclusion: Sahabat cancer a android application can improves the sleep quality of cancer patients. It is necessary to study how to treat cancer patients with sleep disorders at home.